Effect of Water Spinach Spacing and Planting Time on Chili Growth in Chili-Water Spinach Intercropping - Rohmatin Agustina; Tutus Rahmawati; Setyo Budi; Rahmad Jumadi (Jurnal Ilmu Pertanian Indonesia, 2025)
Chili is one of the horticulture crops with the highest commercial value. Farmers can cultivate chili in intercropping systems with water spinach plants as a land-saving alternative. The purpose of this study was to determine the optimal chili planting distance and water spinach planting timing for increasing chili plant growth in chili-water spinach intercropping cultivation. A factorial randomized group design was adopted in this study. The first consideration was the spacing between the chili plants, which measure 50´70 cm and 50´50 cm, respectively. The second aspect was to plant water spinach at the same time as chili, one week after planting (1 WAP) chili, and 2 WAP chili. The findings indicate that optimum spacing and planting time for water spinach can improve the growth of chili plants. When chili plants were spaced 50´70 cm apart, their height and number of leaves increased dramatically. When compared to other treatments, the planting time of water spinach 1-2 WAP chili resulted in significantly higher plant height and number of leaves. All growth variables examined were significantly influenced by the interaction of 50´70 cm and water spinach planting time 2 weeks after chili planting. Keywords: chili, intercropping, planting distance, planting time, water spinach